A phase II multicenter study of the anti-CD19 antibody drug conjugate coltuximab ravtansine (SAR3419) in patients with relapsed or refractory diffuse large B-cell lymphoma previously treated with rituximab-based immunotherapy - Trnĕný, Marek; Verhoef, Gregor; Dyer, Martin Js; Ben Yehuda, Dina; Patti, Caterina; Canales, Miguel; Lopez, Andrés; Awan, Farrukh T; Montgomery, Paul G; Janikova, Andrea; Barbui, Anna M; Sulek, Kazimierz; et al. (Haematologica, 2018)
This phase II, single-arm, multicenter study examined the efficacy and safety of coltuximab ravtansine (an anti-CD19 antibody drug conjugate) in 61 patients with histologically documented (de novo or transformed) relapsed or refractory diffuse large B-cell lymphoma who had previously received rituximab-containing immuno-chemotherapy. Patients had received a median of 2.0 (range 0-9) prior treatment regimens for diffuse large B-cell lymphoma and almost half (45.9%) had bulky disease (≥1 lesion >5 cm) at trial entry. Patients received coltuximab ravtansine (55 mg/m2) in 4 weekly and 4 biweekly administrations until disease progression or unacceptable toxicity. Forty-one patients were eligible for inclusion in the per protocol population. Overall response rate (International Working Group criteria) in the per protocol population, the primary end point, was 18/41 [43.9%; 90% confidence interval (CI:) 30.6-57.9%]. Median duration of response, progression-free survival, and overall survival (all treated patients) were 4.7 (range 0.0-8.8) months, 4.4 (90%CI: 3.02-5.78) months, and 9.2 (90%CI: 6.57-12.09) months, respectively. Common non-hematologic adverse events included asthenia/fatigue (30%), nausea (23%), and diarrhea (20%). Grade 3-4 adverse events were reported in 23 patients (38%), the most frequent being hepatotoxicity (3%) and abdominal pain (3%). Eye disorders occurred in 15 patients (25%); all were grade 1-2 and none required a dose modification. Coltuximab ravtansine monotherapy was well tolerated and resulted in moderate clinical responses in pre-treated patients with relapsed/refractory diffuse large B-cell lymphoma. (Registered at: clinicaltrials.gov identifier: 01472887).
Keywords: dospělí; záchranná terapie; Antigens, CD19; Female; Adult; výsledek terapie; ženské pohlaví; Immunotherapy; lidé; Survival Analysis; difúzní velkobuněčný B-lymfom; Rituximab; Salvage Therapy; Treatment Outcome; Aged, 80 and over; Lymphoma, Large B-Cell, Diffuse; imunokonjugáty; Male; imunoterapie; Aged; antigeny CD19; rituximab; maytansin; analýza přežití; lidé středního věku; humanizované monoklonální protilátky; senioři nad 80 let; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; Maytansine; Immunoconjugates; Middle Aged; Humans